Developing teachers' cultural competencies through co-design of robot-coding mathematics activities for Latinx and Black elementary school students (UCL Press, 2024)
This year-long case study involved the professional development of teachers in New York City elementary schools, who co-designed with researchers culturally relevant robot-coding mathematics activities to advance teachers' understanding of culturally responsive mathematics pedagogy. Study findings indicated that co-designing culturally relevant robot-coding mathematics activities led to the development of teachers' cultural competencies, deeper understanding of culturally responsive mathematics pedagogy and their students' cultures, stronger agency, and ability to integrate culturally responsive pedagogy into their mathematics curriculum. Teachers also began to perceive the robot as a mathematical tool rather than a motivational add-on, and started to develop their own cultural lens while focusing less on school structure constraints. The study emphasises the importance of engaging teachers as active co-designers of culturally relevant coding curriculum in professional development programmes.